The Effect of Advertising and Brand Awareness on Purchasing Decisions for Lemonilo Noodle Products (Case Study on Students of the Faculty of Economics, PASIM National University) - Ayi Muhiban; Nathania Nanda Nugraha (International Journal of Integrative Sciences, 2023)
The purpose of this study was to see how big the effect of advertising and brand awareness on purchasing decisions for Lemonilo Noodle products at Pasim National University. The research methods used are descriptive and associative methods. The unit of analysis in this study were students of the Faculty of Economics, Pasim National University. Based on the results of the sample calculation, 124 respondents were obtained as samples in the study. Multiple linear regression analysis was also carried out using the t test and F test analysis techniques. Based on the research results, the independent variables (advertising and brand awareness) show that there are factors that influence the dependent variable (purchase decision) by 69.8%. The magnitude of the influence of advertising variables on purchasing decisions is 30.6%, and the influence of brand awareness on purchasing decisions is 39.2%